Effect of different routes of magnesium sulfate administration combined with quadratus lumborum block on postoperative analgesia and recovery quality in patients undergoing laparoscopic total hysterectomy: a prospective, randomized controlled trial - Wang, Wen-xiu; Zhang, Li; Zhou, Shu-zhi; Ran, Xin; Zhang, Jie (Frontiers in Medicine, 2025)
ObjectiveTo investigate the effects of different ways of magnesium sulfate injection combined with ultrasound-guided quadratus lumborum block (QLB) on postoperative analgesia and recovery quality of patients undergoing laparoscopic total hysterectomy under general anesthesia.MethodA total of 88 patients who underwent laparoscopic hysterectomy in Ya’an people’s Hospital from June, 2020 to February, 2022, aged from 18 to 65, were randomly divided into three groups: control group (group A, n = 29), local magnesium sulfate group (group B, n = 29) and intravenous magnesium sulfate group (Group C, n = 30) All patients were treated with general anesthesia and patient controlled intravenous analgesia (PCIA) after surgery. General information, visual analogue scale (VAS) at 2 h, 6 h, 12 h, 24 h, 48 h after surgery, dosage of sufentanil in 24 h after surgery, the duration of QLB analgesia (time of first pressing analgesic pump after surgery), 40-item quality of recovery score (QoR-40) before the surgery and on the 3d after surgery, hypotension, bradycardia, postoperative nausea and vomiting (PONV) at 1-3d after surgery, postoperative delirium (POD), skin pruritus, chills, lower limb movement block and other adverse reactions were observed and recorded.ResultCompared with group A, VAS score and postoperative sufentanil consumption were decreased in group B and group C, and the onset time of first postoperative analgesia request was prolonged (p < 0.05), while there was no statistically significant difference between group B and group C (p > 0.05). The QoR-40 score of group B and group C on 3d after surgery was higher than that of group A (p < 0.05), while there was no statistically significant difference between group B and group C (p > 0.05). The incidence of PONV in group B and group C was lower than that of group A, and the difference was statistically significant (p < 0.05), while there was no statistically significant difference between group B and group C (p > 0.05). No hypotension, bradycardia, POD, pruritus, chills, lower limb movement block were observed.ConclusionIntravenous or local use of magnesium sulfate combined with QLB has similar postoperative analgesic effect and promoting postoperative recovery effect in patients undergoing laparoscopic hysterectomy, which can reduce the use of postoperative analgesic drugs, provide effective analgesia and improve the quality of postoperative recovery.Clinical trial registrationChinese Clinical Trial Registry (https://www.chictr.org.cn/), identifier ChiCTR2200055978.